Modelo prospectivo de Gestión Comunicacional Interna para la Unidad Oncológica Solca Chimborazo. - Quintanilla Gaibor, Jessica Carolina (2024)
This research work proposes the design of a prospective internal communication management model for the SOLCA Chimborazo Oncology Unit. The context of this research is to analyze the need to propose this procedure through a prospective model that allows the Institution to improve its internal communication process so that communication and information flow properly, so that employees have a thorough understanding of the institution, its values, their strengths, their objectives, their relevant activities, responsibility towards society and everyone feels committed to their activities and assigned functions. The analysis of the internal communication reality of the Institution has been evidenced through surveys carried out among the staff in which the age range, sex and Management/Department/Unit to which they belong, knowledge of the institution, assessment of internal communication and use of tools, communication with employees, communication with the immediate superior and his or her existing relationship with his collaborators. The importance of the study carried out lies in the fact that currently at SOLCA Chimborazo there is no formal internal communication process; Therefore, the methodology used in this research uses a mixed approach since it will collect and analyze quantitative and qualitative data; The research design is non-experimental, because none of the variables will be modified with any technique or tool and the type of research is field and transversal to achieve a level of descriptive research.